The relationship between stock market volatility and macroeconomics volatility in Malaysia / Mohammad Izzat Azahar - Azahar, Mohammad Izzat (Faculty of Business Management, 2015)
Stock market is an indicator of an economy financial health. It indicates the mood of investors in a country. As such, stock market development is an important ingredient for growth. The study is considers macroeconomic variables as Gross Domestic Product (GDP), inflation, exchange rate, interest rate and money supply. Macroeconomic variables play a vital role in the economic performance of any country. The changes or volatility of macroeconomics will affects the volatility of stock market in Malaysia. Every year and every country faced that change of macroeconomics in their country.